Abiotic and Biotic Factors Influencing Sugar Maple Health: Soils, Topography, Climate, and Defoliation. Issue 6 (11th November 2014) - Pitel, Nicholas E.; Yanai, Ruth D.
Abstract : Sugar maple ( Acer saccharum Marsh.), a keystone species of northern hardwood forests, is susceptible to decline, especially on sites low in the soil base cations calcium (Ca) and magnesium (Mg). A common stressor of sugar maple is forest tent caterpillar (FTC; Malacosoma disstria Hübner), an indigenous defoliator. The recent outbreak of FTC (2002–2007) affected 600, 000 ha of forest in the northeastern United States and Canada. We assessed the condition of sugar maple trees in 47 North American Maple Project stands in Massachusetts (2006–2007) and Vermont and New York (2007–2008) just after the peak of the FTC outbreak. Mortality was highest in stands with the most crown dieback the previous year ( R 2 = 0.62, P < 0.001). In addition to drought, cold winter temperatures, and concave microrelief, mortality reflected an interaction of defoliation with soil base cation availability ( P = 0.02), with stands defoliated in 2005 that also had low Mg saturation in the A horizon being most likely to suffer high mortality. Sites with above‐average annual sugar maple mortality (>3 or 4%) occurred on soils with low concentrations of Ca (0.31–0.46 cmolc kg −1 in the upper B horizon), Mg (0.06–0.10 cmolc kg −1 ), and K (0.03–0.05 cmolc kg −1 ). This work extends the thresholds for these base cations determined by previous research on the Allegheny Plateau to a larger geographic area.